Comparison of forecasting performances: Does normalization and variance stabilization method beat GARCH(1, 1)‐type models? Empirical evidence from the stock markets. (16th June 2017) - Gulay, Emrah; Emec, Hamdi
Abstract: In this paper, we present a comparison between the forecasting performances of the normalization and variance stabilization method (NoVaS) and the GARCH(1, 1), EGARCH(1, 1) and GJR‐GARCH(1, 1) models. Hence the aim of this study is to compare the out‐of‐sample forecasting performances of the models used throughout the study and to show that the NoVaS method is better than GARCH(1, 1)‐type models in the context of out‐of sample forecasting performance. We study the out‐of‐sample forecasting performances of GARCH(1, 1)‐type models and NoVaS method based on generalized error distribution, unlike normal and Student's t ‐distribution. Also, what makes the study different is the use of the return series, calculated logarithmically and arithmetically in terms of forecasting performance. For comparing the out‐of‐sample forecasting performances, we focused on different datasets, such as S&P 500, logarithmic and arithmetic BİST 100 return series. The key result of our analysis is that the NoVaS method performs better out‐of‐sample forecasting performance than GARCH(1, 1)‐type models. The result can offer useful guidance in model building for out‐of‐sample forecasting purposes, aimed at improving forecasting accuracy.